Efektifitas Sustained Natural Apophyseal Glides (SNAGS) Terhadap Penurunan Nyeri Pada Kasus Nyeri Leher - Santoso, Iman; Karnadipa, Triana; Noviana, Mita; Sakinah, Ummulkhair (UI Scholars Hub, 2022)
Neck pain attacks 16.6% of the general adult population in Indonesia. This condition causes disruption of function and motion in the neck, so it requires physiotherapy intervention. Sustained Natural Apophyseal Glides (SNAGs) is a mobilisation with movement techniques that can decrease pain during exercise without causing any secondary pain. Materials and Methods. From the search results with various databases found 385 journals that match these keywords, screened titles and abstracts were found 30 articles were then filtered and 20 articles were selected. However, from the 20 articles, there will be further screening. The final result after selection is 5 articles. Results. Of the five articles reviewed on Sustained Natural Apophyseal Glides (SNAGs) using a dose of 3 sets of 6 repetitions per training session with the method of Gliding can reduce pain in the cases of neck pain. Conclusion. The Mulligan Concept Exercise with the Sustained Natural Apophyseal Glides (SNAGs) technique using a dose of 3 sets of 6 repetitions per training session with the method Gliding according to the direction of movement experiencing pain can produce a positive effect on reducing pain in cases of neck pain so that it can restore motion function on the neck.